The Impact of the Source Language in Spanish Translations: A Survey on English Counterfactuals ‘Should have’ - Repiso, Isabel (Meta, 2018)
The present article shows that the most frequent way of translating Should have + Past participle in Spanish is the word-by-word translation Debería haber. This preference is not coherent with the language use of natives at three levels: (i) the marginal role of modal verbs to express the speaker’s subjectivity in Spanish; (ii) the preferred use of modal verbs in the past participle position (e.g., No hubiese debido tener libros); and (iii) the predominant use of the pluperfect subjunctive as a prompting tense for counterfactual readings. Our survey is based on 1.7  million-word Social Sciences corpus covering 8 essays, 4 political biographies and 2 dystopian novels. In all, 9  sentences containing should have + past participle were analyzed. The translations were crossed with a reference corpus in Spanish containing 154 million words (CREA). The translators’ preference by Debería haber has an effect in the output texts’ readability since it implies a reversal in the frequencies of the Spanish constructions pertaining to the irrealis semantic domain. Our results provide empirical cues to prevent the word-by-word translation Debería haber, such as avoiding infinitive periphrastic constructions or favoring subjunctive mood’s tenses.